Hydrogen embrittlement of DP‐1000 flat steel sheet: Influence of mechanical properties, specimen geometry, pre‐damaging and electrolytically zinc galvanizing. Issue 3 (27th July 2015) - Scharf, R.; Muhr, A.; Luckeneder, G.; Larour, P.; Mraczek, K.; Rehrl, J.; Leomann, F.; Stellnberger, K.‐H.; Faderl, J.; Mori, G.
Abstract : Studies towards the impact of solute hydrogen on the mechanical properties of ultra‐high strength sheet steel grades (UHSS) for the automotive industry have been increasingly conducted in the past years. This paper focuses on the pre‐damaging of a dualphase DP‐1000 automotive sheet steel, as found in the manufacturing of automotive body parts, in connection with hydrogen embrittlement. It is shown that the kind of pre‐damaging of the specimens has a severe influence on the occurrence of hydrogen embrittlement. Hydrogen embrittlement resistance under corrosive conditions was determined through constant load tests. Tensile specimens, manufactured from electrolytically zinc galvanized DP‐1000 steel, were immersed in a 5% sodium chloride solution. The impact of material properties, pre‐damaging and specimen geometry are critically discussed. Furthermore a discussion is given about the material testing methods most suitable to indicate high or low hydrogen embrittlement resistance if constant load testing is performed.